A Systematic Review: A Model of Social-Community Intervention to Reduce Early Marriage in West Nusa Tenggara - Ratin Wahyu Juni Atma (Chatra: Jurnal Pendidikan dan Pengajaran, 2026)
Early marriage is a marriage that occurs at an age below the minimum limit regulated by law. Early marriage is a form of violation of the child's right to grow and develop. This problem is an important social problem in West Nusa Tenggara (NTB). This study aims to systematically review various social-community intervention models applied to prevent early marriage practices, especially in NTB. This research method uses a systematic review prepared using the PRISMA 2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The stages of PRISMA 2020 are identifying, selecting, assessing, and synthesising literature. In this literature review, we identify the factors that cause early marriage, the types of social-community interventions, the implementing actors, and the interventions' impact. Therefore, the most effective intervention model for reducing the number and preventing early marriage is one that integrates social-community with legal education, and targets changes in values among figures who play a role as drivers of new norms to support the age of child marriage after maturity or regulation. This research can serve as a reference for developing a model of social-community intervention that addresses the root causes of early marriage.Pernikahan dini adalah pernikahan yang terjadi pada usia di bawah batas minimum yang diatur oleh hukum. Pernikahan dini merupakan bentuk pelanggaran terhadap hak anak untuk tumbuh dan berkembang. Masalah ini menjadi persoalan sosial yang penting di Nusa Tenggara Barat (NTB). Penelitian ini bertujuan untuk meninjau secara sistematis berbagai model intervensi sosial-komunitas yang diterapkan untuk mencegah praktik pernikahan dini, khususnya di NTB. Metode penelitian ini menggunakan systematic review yang disusun berdasarkan pedoman PRISMA 2020 (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Tahapan PRISMA 2020 meliputi identifikasi, seleksi, penilaian, dan sintesis literatur. Dalam kajian literatur ini, diidentifikasi faktor-faktor penyebab pernikahan dini, jenis intervensi sosial-komunitas, aktor pelaksana, serta dampak dari intervensi tersebut. Oleh karena itu, model intervensi yang paling efektif untuk menurunkan angka dan mencegah pernikahan dini adalah model yang mengintegrasikan pendekatan sosial-komunitas dengan edukasi hukum, serta menargetkan perubahan nilai pada tokoh-tokoh yang berperan sebagai penggerak norma baru guna mendukung usia pernikahan yang sesuai dengan kematangan atau ketentuan regulasi. Penelitian ini dapat menjadi rujukan dalam pengembangan model intervensi sosial-komunitas yang mampu menyasar akar permasalahan pernikahan dini.